High Expression of CLEC11A Predicts Favorable Prognosis in Acute Myeloid Leukemia - Yin, Chengliang; Zhang, Junyan; Guan, Wei; Dou, Liping; Liu, Yuchen; Shen, Ming; Jia, Xiaodong; Xu, Lu; Wu, Rilige; Li, Yan (Frontiers in Oncology, 2021)
Abstract Background: Acute myeloid leukemia (AML) is a heterogeneous disorder of hematopoietic system. Identifying novel biomarkers is an urgent clinical need and research hotspot for treatment optimization. Methods: C-type lectin domain family 11, member A (CLEC11A) was selected via several public databases by comparing expression among a variety of tumors and normal samples as well as different organs and tissues. An AML cohort derived from TCGA was used to investigated the relationship between CLEC11A expression and clinical characteristics. We also investigated Bloodspot and HemaExplorer database. Kaplan-Meier method and log-rank test were utilized to evaluate the associations between CLEC11A mRNA expression and DNA methylation, also their associations among overall survival (OS), event-free survival (EFS), relapse-free survival (RFS). Bioinformatics analysis of CLEC11A was carried out in public databases. Results: Our study provided evidences about CLEC11A as a tumor suppressor gene that CLEC11A mRNA expression was high in AML and associated with favorable prognosis. The results of TCGA data showed that high CLEC11A expression was associated with favorable prognosis (OS p-value = 2e-04; EFS p-value = 6e-04), which was further validated in GSE6891 (OS p-value = 0; EFS p-value = 0; RFS p-value = 2e-03). High CLEC11A methylation levels group was linked to poorer prognosis (OS p-value = 1e-02; EFS p-value = 2e-02). Meanwhile, low CLEC11A DNA methylation level was associated with AML induction remission and short survival. Bioinformatic analysis also showed that CLEC11A was an up-regulated gene. Conclusion: CLEC11A may serve as an effective prognostic biomarker, and could provide valuable treatment indications for AML patients, whose distinctive gene patterns were helpful to further understand the heterogeneous mechanisms for AML. Keywords: Acute myeloid leukemia, prognostic biomarker, CLEC11A.